Is there light at the end of the tunnel?—new perspectives in ECMO survival - Pappalardo, Federico; Montisci, Andrea (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Cardiogenic shock (CS) is a state of systemic hypoperfusion, secondary to a deficit in cardiac contractile activity. Acute myocardial infarction (AMI) accounts for the majority of cases of CS, with a high mortality rate, despite the great improvements in revascularisation therapy. Nowadays, mechanical circulatory support (MCS) in CS often represents the only therapeutic approach able to restore systemic perfusion, determining a survival benefit. Recently, many efforts have been made to identify factors associated with mortality in patients receiving MCS devices. New insights into the pathophysiology of CS prompted the concept that the use of MCS should be considered early in the course of the disease, before the progression to multiorgan dysfunction. However, many questions remain unsolved and randomised trials in this field are hard to perform. Looking at the future, the timely implantation of temporary MCS, the correct selection of patient, the concomitant use of different temporary devices, the improvement in weaning strategies and the increasing use of durable devices as a destination or bridge therapy appear to be the most promising areas of development.